Morphology and histoenzymology of eosinophilic granulocytes in the circulating blood of the turtle (Chrysemys dorbignih) - Azevedo, A. [UNESP]; Casaletti, L.; Lunardi, L. O. (My University, 2002)
The studies on the characterization of eosinophils and neutrophils/ heterophils of turtles are contradictory. Some authors have pointed out the existence of two distinct cell types: eosinophils and heterophils. Other authors have proposed that eosinophils and heterophils may be the same cells in different stages of maturation. These interpretations are based only on a morphological analysis. In the blood of the turtle (Chrysemys dorbignih), a South American freshwater species, there are two types of granulocytes with eosinophilic staining pattern: the first with round cytoplasmic granules and the second with ellipsoidal cytoplasmic granules. In the present study by using histoenzymological methods for the analyses of enzymological cellular content, we found that the cells with round cytoplasmic granules were positive for nonspecific esterase and the cells with ellipsoidal granules were positives for acid phosphatase, alkaline phosphatase, nonspecific esterase and peroxidase. The results show that these cells are distinct cells and that the cells with ellipsoidal cytoplasmic granules have the same histoenzymological characteristics as the neutrophils/heterophils of mammalians and other vertebrates.
Keywords: Granulocytes; Histoenzymology; Leukocytes; Turtle; Ultrastructure; acid phosphatase; alkaline phosphatase; esterase; fresh water; peroxidase; carboxylesterase; animal cell; blood chemistry; cell granule; cell interaction; cellular distribution; chrysemys dorbignih; circulation; controlled study; enzymology; eosinophil; granulocyte; histology; micromorphology; neutrophil; nonhuman; technique; turtle; animal; chemistry; cytochemistry; cytology; electron microscopy; physiology; ultrastructure; Animalia; Chrysemys; Mammalia; Testudines; Vertebrata; Acid Phosphatase; Alkaline Phosphatase; Animals; Carboxylesterase; Carboxylic Ester Hydrolases; Cytoplasmic Granules; Eosinophils; Histocytochemistry; Microscopy, Electron; Peroxidase; Turtles